Thrombectomy for distal medium vessel occlusion with a new generation of Stentretriever (Tigertriever 13). Issue 4 (August 2022) - Guenego, Adrien; Mine, Benjamin; Bonnet, Thomas; Elens, Stephanie; Vazquez Suarez, Juan; Jodaitis, Lise; Ligot, Noémie; Naeije, Gilles; Lubicz, Boris
Purpose: To evaluate the safety and efficacy of the Tigertriever 13 (Rapid Medical, Yoqneam, Israel) stent retriever in acute ischemic stroke (AIS) patients with primary or secondary distal, medium vessel occlusions (DMVO). Methods: We performed a retrospective analysis of all consecutive AIS patients who underwent thrombectomy with the Tigertriever13 for DMVO. Patients' characteristics were reviewed, procedural complications, angiographic (modified thrombolysis in cerebral infarction score [mTICI]) and clinical (modified Rankin Scale [mRS]) outcomes were documented. Results: Between November 2019 and November 2020, 16 patients with 17 DMVO were included (40% female, median age 60 [50–65] years). The Tigertriever13 was used in 11/17 (65%, median NIHSS of 8 [6–15]) primary DMVO and in 6/17 (35%, median NIHSS of 20 [13–24]) cases of secondary DMVO after a proximal thrombectomy. The successful reperfusion rate (mTICI 2b, 2c, 3) was 94% (16/17) for the dedicated vessel. At day 1, CT imaging showed a subarachnoid hemorrhage in 29% of the cases and a parenchymal hematoma in 12%. At 3 months, 65% of the patients (11/17) had a favorable outcome (mRS 0–2). Conclusion: Mechanical thrombectomy using the Tigertriever13 appears to be safe and effective for DMVO. Clinical and anatomical results are in line with those of patients with proximal occlusions.